Kajian Efisiensi dan Karakterisasi Produksi Ozon dengan Lucutan Plasma Berpenghalang Dielektrik (DBDP) untuk Pengendalian Jamur dalam Beras - Rachman, Dian Arif; Nur, Muhammad; Kusdiyantini, Endang (BERKALA FISIKA, 2014)
A research about the influence of ozone on fungi  which living on rice type mentik that used natrium agar (TPC methode) media has done.  The research was done at normal temperature and the outside air pressure with free air as a source of ozone. The ozone concentration of 2.91 up to 3.19 ppm was radiated on 7 differnet samples of rice, each sample 50 gram used ozonized  time variation 0 minutes, 30 minutes, 60 minutes, 90 minutes, 120 minutes, 150 minutes and 180 minutes. It was obtained results the number of fungi that died of 97,3 % after ozone irradiated for 30 minutes and 99,2% after 60 minutes. Total number of fungi which has dead during 150 minutes as much 99,9 %. Characterization of ozone conducted using ozone reactor (Dielectric Barrier Discharge Plasma). variation in the voltage and the rate of air flow was performed to obtain the optimum concentration of ozone. Voltage variation started from 6 kV, 6 kV, 8 kV and 6 kV whereas variation of oxygen flow rate of 0.5 L/min, 1 L/min, 2 L/min and 3 L/minute. The results obtained with the same tendency which is that at the same voltage, the higher the air flow rate and declining concentrations of ozone. On the study for flow rate of 0.5 L/min the ozone concentrations was obtained 4.6 up to 6.8 ppm. While for flow rate of 3 L/minute ozone concentrations was obtained 2.9 up to  4.8 ppm. Keywords: fungi, natrium agar, irradiate, reactor